Shock processing of amorphous carbon nanodust. Issue 8 (15th October 2022) - Roy, Arijit; Singh, Surendra Vikram; Ambresh, M.; Sahu, D.; Meka, J.K.; Ramachandran, R.; Samarth, P.; Pavithraa, S.; Jayaram, V.; Hill, H.; Cami, J.; Rajasekhar, B.N.; et al.
Abstract: Our understanding on the role of amorphous carbon in the interstellar medium to form complex structures, such as carbon nanotube/graphene/fullerene, is limited to date. We have investigated how shocks may induce physico-chemical transformation in amorphous carbon by subjecting samples of carbon nanopowder to high-temperature shocks, ∼7300 K, in a hydrogen-free environment for about 2 ms using a shock tube. The shock conditions achieved in the laboratory mimics low velocity interstellar shocks. Post shock samples were analyzed using Raman Spectroscopy and High Resolution – Transmission Electron Microscopy. We have found compelling evidence for the formation of carbon nanotube, graphene, and various other carbon nanostructures induced by the shock. Our results show that shocks in the interstellar medium can provide important chemical pathways to the formation of fullerenes and suggests that other carbonaceous structures may be present as well.